2011
DOI: 10.1002/acp.1765
|View full text |Cite
|
Sign up to set email alerts
|

Associations between evaluation anxiety, cognitive interference and performance on working memory tasks

Abstract: According to Cognitive Interference Theory, evaluation anxiety leads to increased negative off-task self-dialogue which then results in diminished cognitive performance. Given that negative off-task self-dialogue is primarily verbal, the phonological loop and central executive components of the working memory system should be most affected by evaluation anxiety. Eighty-eight participants were randomly assigned to receive evaluation anxiety inducing instructions or supportive instructions prior to administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(43 citation statements)
references
References 34 publications
3
38
0
1
Order By: Relevance
“…This accounts for the stressful effect of the SCW task with interference used during the anxiogenic condition as observed in previous works in healthy individuals 27. Adding time pressure, failure feedback and video recording to a task requiring attentional load during the anxiogenic condition thus induced more anxiety in all participants compared to the neutral condition 9 29. In addition, state anxiety was more pronounced in patients with stroke than in control subjects both under neutral and anxiogenic conditions while being similar during the baseline.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This accounts for the stressful effect of the SCW task with interference used during the anxiogenic condition as observed in previous works in healthy individuals 27. Adding time pressure, failure feedback and video recording to a task requiring attentional load during the anxiogenic condition thus induced more anxiety in all participants compared to the neutral condition 9 29. In addition, state anxiety was more pronounced in patients with stroke than in control subjects both under neutral and anxiogenic conditions while being similar during the baseline.…”
Section: Discussionsupporting
confidence: 62%
“…This issue is particularly relevant in patients with stroke without severe cognitive impairment who may experience high levels of anxiety3 4 and working memory impairments1 as foreground symptoms which could interfere both with subsequent rehabilitation5 6 and return to work 7 8. It is important to take into consideration that in the acute phase of stroke, stressful events can occur during hospitalisation (eg, medical examination, announcement of diagnosis, neuropsychological assessment3 9), which could increase state anxiety. It is therefore essential to ask whether the possible disruption of working memory in patients with acute stroke is due to working memory impairments per se or to the negative impact of anxiety on working memory or both.…”
Section: Introductionmentioning
confidence: 99%
“…The visuospatial sketchpad is thought to be involved in the temporary storage and manipulation of visual information, while the central executive is chiefly responsible for attention-related functions. According to attentional control theory, anxiety is thought to primarily impact on two of these central executive functions, which include inhibition (the suppression of task-irrelevant stimuli), attentional shifting (ability to shift attention between multiple tasks), and the phonological loop (Derakshan & Eysenck, 2009), but not the visuospatial sketchpad (Coy, O'Brien, Tabaczynski, Northern, & Carels, 2011). The components of working memory have been demonstrated to play an important role in academic outcomes (Alloway, 2011).…”
Section: The Working Memory Systemmentioning
confidence: 98%
“…Previous research has found that emotional stimuli capture and hold our attention, and that such emotional interference may impair task performance (Huang, Baddeley, & Young, 2008;Ihssen & Keil, 2009). In addition, cognitive interference consists of intrusive, off-task thoughts that may also compete with relevant cognitive processing and affect working memory and recall performance (Coy, O'Brien, Tabaczynski, Northern, & Carels, 2011;Ellis, Moore, Varner, Ottaway, & Becker, 1997). The resource allocation model (Ellis & Ashbrook, 1988) suggests that emotional states draw on a part of an individual's ability to focus attention, weakening performance on tasks that require concerted attention (e.g., recall of information).…”
Section: Love As Interferencementioning
confidence: 99%